186k views
3 votes
Find the general solution of the differential equation: y' + 3x^2 y = 0

1 Answer

6 votes

Answer:

The general solution of the differential equation y' + 3x^2 y = 0 is:


y=e^(-x^3+C)

Explanation:

This equation its a Separable First Order Differential Equation, this means that you can express the equation in the following way:


(dy)/(dx) = f_1(x)*f_2(x), notice that the notation for y' is changed to
(dy)/(dx)

Then you can separate the equation and put the x part of the equation on one side and the y part on the other, like this:


(1)/(f_2(x))dy=f_1(x)dx

The Next step is to integrate both sides of the equation separately and then simplify the equation.

For the differential equation in question y' + 3x^2 y = 0 the process is:

Step 1: Separate the x part and the y part


(1)/(y)dy=3x^2}dx

Step 2: Integrate both sides


\int(1)/(y)dy=\int 3x^2}dx

Step 3: Solve the integrals


Ln(y)+C=-x^3+C

Simplify the equation:


Ln(y)=-x^3+C

To solve the Logarithmic expression you have to use the exponential e


e^(Ln(y))=e^(-x^3+C)

Then the solution is:


y= e^(-x^3+C)

User Giancarlos
by
6.3k points